Performance Analysis of Direct Torque Control of Induction Machines - Raja Yunus , Raja Nor Azrin; Jidin , Auzani; Alias, Nor Faezah; Lukar Herlino, Adeline; Manap, Mustafa (2013)
This paper presents the study of effects of hysteresis controllers on performance of Direct Torque Control (DTC) of induction machines. By analyzing the DTC performances through simulations, it can provide useful information for the beginner researchers to identify the root of problems and hence chooses the appropriate hysteresis bandwidths for any operating conditions to achieve high DTC performances. It should be noted that the DTC drive has gained widely acceptance for many industrial applications due to its simplicity. However, the DTC which is based on hysteresis comparators has two major drawbacks, namely variable switching frequency and larger torque ripple. It can be shown that the DTC performance may deteriorate if the inappropriate flux and torque bandwidths are chosen. This research is aimed to analyze DTC performances in terms of total harmonic distortion (THD), torque ripple and switching frequency for variations of controller hysteresis bandwidths and operating conditions. The problems which are mainly associated in hysteresis controllers were identified by simulating the DTC of induction machine at different applications of hysteresis bandwidth, sampling frequency and operating conditions (e.g. different of load torque or speed levels). This study provides the consideration for the designer in choosing appropriate bandwidth to have high performance of DTC drives.